Modern cyclophane chemistry - Gleiter, Rolf (Wiley-VCH Verl., 2004)
Here, the editors Rolf Gleiter and Henning Hopf present an excellent overview of all the important aspects and latest results in cyclophane chemistry. Clearly structured and covering the entire range, the book introduces readers to the most recent research in the field. Twenty chapters, written by well-known scientists, cover in particular: synthesis of carbo- and heterocyclic cyclophanes and metallocenophanes; structural and spectroscopic properties of cyclophanes; current and future applications in synthesis and material science; novel reactions of cyclophanes; use of cyclophanes as building
Includes bibliographical references and index. - Print version record
Keywords: Electronic books; Cyclophane